CAUSAL FACTORS AFFECTING BUSINESS MODEL INNOVATION AND SUSTAINABLE PERFORMANCE OF MONTHLY RENTAL APARTMENTS IN THAILAND - Thanusak Loogsorn, (PEOPLE: International Journal of Social Sciences, 2025)
This dissertation investigates the causal factors influencing business innovation models and sustainable performance in Thai apartments. The research aims to explore the impact of key factors, including green leadership, digital service transformation, and internal capabilities, on business innovation and sustainability. A comprehensive theoretical framework integrates these components using a systemic analysis that highlights the interconnections between each variable. Findings reveal that green leadership significantly enhances environmentally friendly practices and green innovation, while digital transformation improves operational efficiency and competitive advantage. Internal capabilities foster ongoing innovation and sustainability, contributing to a business model responsive to market and environmental demands, leading to long-term sustainability. This study provides valuable insights for apartment entrepreneurs, academics, and researchers, supporting sustainable business practices in Thailand's real estate sector.